PENGARUH MACAM LIMBAH RUMAH TANGGA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM MANIS (Sorghum bicolor (L.) Moench) - Muchtarom Almutakkabbir; Sartono Joko Santosa; Kharis Triyono (Innofarm:Jurnal Inovasi Pertanian, 2020)
The research about study of the effects of household waste on the growth and yield of sweet sorghum plants (Sorghum bicolor (L). Moench), with aim to know the effects of the use of household waste on the growth and yield of sweet sorghum plants (Sorghum bicolor (L). Moench), had been done from 01 October 2019 to 21 January 2020, in experimental garden of the Faculty of Agriculture, University of Slamet Riyadi Surakarta, in the village of Mojosongo, Banjarsari sub-district, Surakarta with an increase in ± 143 places (masl). The  method of research used a single Completely Random Desaign (CRD) consisting of 10 treatments, each treatment was repeated 3 times. Kind of waste household is tea water waste, coffee water waste and rice washing water waste. Data from the research were analyzed with the BNJ test (Honestly Significant Difference) at a level of 5%. The parameters observed were included height of plant, number of leaves, length of leaves, fresh straw weight of biomass, dry straw weight of biomass, seeds totals per plant, weight dry seeds per plant, weight of 100 dry seeds per plant. The result of the research showed that : (1) the treatment of household waste that is coffee waste with a content of 50% (C1) has a significant effect on the parameters height of plant, number of leaves, length of leaves, seeds totals per plant, and weight of 100 dry seeds per plant. (2) the coffee waste treatment with a content of 50% (C1) yields the highest height of plant is 297,50 cm, the highest number of leaves is 18,83 sheet, the longest length of leaves is 146,50 cm, the highest seeds totals per plant is 3517,33 grain, weight dry seeds per plant is 112,27 gram, and the weight of 100 dry seeds per plant is 3,79 gram. (3) the treatment that  is coffee waste with a content of 50% provides the highest growth and yield in sorghum plants.